Union Wage Differentials in the Public and Private Sectors: A Simultaneous Equations Specification - Robinson, Chris; Tomes, Nigel (Journal of Labor Economics, 1984)
The paper attempts to integrate new approaches to estimating union wage effects with the analysis of public-private sector wage differentials. Estimates of the union differential in both public and private sectors, allowing for the endogeneity of union status, are presented. The hypothesis that the recently measured rents to public sector employment primarily reflect the recent increase in unionization in that sector is examined, and receives considerable empirical support. There was evidence of positive selection into the union sector, especially for private sector workers. Union status appears to be strongly influenced by the expected wage gain from joining the union sector.